A Direct Discrete-Time Reduced Order Robust Model Reference Adaptive Control for Grid-Tied Power Converters with Lcl Filter - Evald, Paulo J. D. O.; Tambara, Rodrigo V.; Gründling, Hilton A. (Eletrônica de Potência, 2020)
In this work is presented the design of a direct discrete-time reduced order RMRAC (Robust Model Reference Adaptive Control) applied to the grid-side current control of a static grid-tied voltage-fed 3-wire converter with LCL filter. The proposed controller tracks the reference model output as close as a higher order RMRAC, with similar performance. Furthermore, it rejects exogenous disturbances from grid without the need of conventional resonant controllers, often employed in this kind of application. To design the reduced order controller, the LCL filter is approximated to a first order transfer function, neglecting the capacitor influence. Besides, it is shown mathematically that capacitor is the main element that compounds the additive dynamics, which is considered as unmodelled dynamics to design the controller. Furthermore, experimental results performed in a TMS320F28335 Delfino microcontroller are presented and show the similarity of performance between proposed control method and higher order RMRAC, regarding to harmonics content, which indicate its feasibility.